System dynamics modeling for tooth decay treatment in Brazilian children - Josely Emiko UMEDA; Karim CHICHAKLY; Guttenberg Ferreira PASSOS; Raquel Sano Suga TERADA; Renata Corrêa PASCOTTO; Mitsue FUJIMAKI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Prevention and health promotion are considered important strategies to control oral diseases. Dental caries is preventable disease and remains the most common chronic disease that affects mainly low income children and still considered the main cause of tooth loss in adulthood in Brazil. The aim of this study is to present a System Dynamics model (SDM) specifically developed with the Stella Architect software to estimate the cost and clinical hours required to control the evolution of dental caries in preschool children in Maringá, Brazil. Two main strategies to control caries were considered in the model: the application of fluoride varnish on teeth presenting white spots, and the use of Atraumatic Restorative Treatment (ART) in cavitated carious lesions without pulp involvement. The parameters used in the model were: number of people covered by a local oral health team = 4,000; number of children up to 5 years = 7% of the population; children's decayed, missing, filled teeth (dmft) index = 2.4; time/cost of 4 applications of fluoride varnish = 5 minutes/US$ 0.716; and time/cost of each ART restoration = 15 minutes/US$ 1.475. The SDM generated an estimated total cost of US$698.00, and a total of 112 clinical hours to treat the population in question. The use of the SDM presented here has the potential to assist decision making by measuring the material and human resources required to prevent and control dental caries at an early age.